Vermicompost growth and uptake in Carludovica palmata R. & P. in Campeche, Mexico - Ortega-Haas, Juan José; Pat-Fernández, Juan Manuel; Gómez-Álvarez, Regino; Manzanero-Acevedo, Luis Ariel (REVISTA TERRA LATINOAMERICANA, 2020)
Vermicompost is an organic fertilizer that increases soil fertility and crop productivity. The use of this organic fertilizer in Jipijapa (Carludovica palmate) palm productivity is a low-cost and environmentally-friendly alternative. Therefore, the objective of this study was to evaluate vermicompost effects on leaf growth development of leaf growth of C. palmate for 120 days in an experimental plot located in Santa Cruz Ex-Hacienda, Calkiní, Campeche, Mexico. The experiment was based on Latin Square Design with six treatments and six replications. Treatments with vermicompost were applied in different doses (T1 = 0 Mg ha-1; T2 = 5.3 Mg ha-1; T3 = 10.6 Mg ha-1; T4 = 15.9 Mg ha-1; T5 = 10.6 Mg ha-1 of vermicompost + 0.22 Mg ha-1 of Triple 17 and T6 = 0.22 Mg ha-1 of Triple 17 EM®. The application of vermicompost had no significant differences on total number of leaves per hole and number of shoot of Jipi palm compared to the control (P > 0.05). The frequency in the stages of shoot and opened leaves were significantly different for T4 and T5. The beneficial effects of Vermicompost were in growth and shoot development, leaf, petiole, and blade length, and less mortality in leaves.